Onychomycosis in Israel: epidemiological aspects. Issue 3 (15th January 2015) - Segal, Rina; Shemer, Avner; Hochberg, Malca; Keness, Yoram; Shvarzman, Rima; Mandelblat, Marina; Frenkel, Michael; Segal, Esther
Summary Onychomycosis is a fungal infection treated orally for prolonged periods of treatment, caused primarily by Dermatophytes, Candida species and non‐dermatophyte moulds (NDMs). The prevalence of specific aetiology may differ in dependence of environmental, geographic and demographic factors, and may affect management of the infection. The objective of this survey was to analyse epidemiologic parameters of onychomycosis in Israel. Data of a cohort of 27 093 patients were collected from six centres during a 2‐ and 10‐year period. The diagnosis was based on microscopy of KOH/calcofluor mounts of nail scrapings and culture isolation. A positive result indicates isolation of a fungus in culture. Data were analysed for each centre and expressed as range for the whole cohort, using the spss v18 software. Analysis included three epidemiologic parameters: fungal aetiology in toe‐ and fingernails; association with gender; association with age group. Dermatophytes were the major causative agents and Trichophyton rubrum the most frequent isolate. Candida species were more frequent in women fingernails; frequency increased with age and C. parapsilosis the most frequent species. NDMs were isolated at low rate and Aspergillus terreus was the most frequent isolate. This is a first large cohort of onychomycosis patients from Israel analysed by defined epidemiological parameters.